Ablation Patterns of the Debris Covered Tongue of Halong Glacier Revealed by Short Term Unmanned Aerial Vehicle Surveys - Guo, Wanqin; Guo, Xiaojun; Liu, Yushuo; Li, Jing; Shangguan, Donghui; Chen, Liqun; Ga, Jin (Frontiers in Earth Science, 2021)
Debris covered glacier is an important glacier type and has attracted more and more attentions. This study presents the results of ablation patterns of debris covered tongue of Halong Glacier in northeastern Tibetan Plateau, by using two repeated unmanned aerial vehicle (UAV) surveys performed on August 11 and September 15, 2019. The results show that the tongue of Halong Glacier has experienced strong ablation during the surveyed period, with an overall ice loss amount to 4.17×105 ton w.e.. Among all the briefly classified surface types, supraglacial debris has the largest area (80.9%) and also mass losses (58.6%) comparing to others. However, ice cliffs show the strongest and the most significant ablation rates (averagely 1.36 m w.e. and 1.22 m w.e. for supraglacial and lateral ice cliffs, respectively), followed by clean ice regions (1.01 m w.e.). The backwastes of ice cliffs also resulted in up to 7.8 m horizontal back-off at different parts of Halong Glacier, lead to fast terminal retreat and also narrowing down of the glacier tongue, and may result in break off of Halong Glacier tongue into separated parts in future. The surface ablation rates show clear negative exponential relationship with the measured debris thicknesses, in well accordance with previous studies. Regions in cutting and flushing by supraglacial and lateral rivers have the largest surface elevation decreases but not significant due to their limited area and the relatively lower quality of UAV digital surface models (DSMs) in those covered regions.